2018
DOI: 10.1007/978-3-319-65798-1_44
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight-Induced Visual Impairment and Globe Deformations in Astronauts Are Linked to Orbital Cerebrospinal Fluid Volume Increase

Abstract: These findings are evidence for the primary role of CSF and a lesser role for intracranial cephalad fluid-shift in the formation of VIIP. VIIP is caused by a prolonged increase in orbital CSF spaces that compress the globes' posterior pole, even without a large increase in ICP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…60 The ongoing debate has prompted revisiting some of the other risk factors including carbon dioxide and in particular the role of hypercapnia in increased ICP and in terrestrial analogs (e.g., head down tilt studies) that may mimic the cephalad fluid shift. Renewed interest in the role of ICP [60][61][62][63][64][65][66][67][68][69] in SANS has led to discussion about the feasibility of performing a lumbar puncture in space despite the obvious logistical and operational challenges to an in-flight invasive procedure. [70][71][72] Non-invasive assessment of ICP have not been reliably validated on earth but ultrasound is available on the ISS and the possibility of ultrasonographic metrics (e.g., optic nerve sheath diameter, CSF in the sheath) remain an area of continued research.…”
Section: Oct and Sansmentioning
confidence: 99%
“…60 The ongoing debate has prompted revisiting some of the other risk factors including carbon dioxide and in particular the role of hypercapnia in increased ICP and in terrestrial analogs (e.g., head down tilt studies) that may mimic the cephalad fluid shift. Renewed interest in the role of ICP [60][61][62][63][64][65][66][67][68][69] in SANS has led to discussion about the feasibility of performing a lumbar puncture in space despite the obvious logistical and operational challenges to an in-flight invasive procedure. [70][71][72] Non-invasive assessment of ICP have not been reliably validated on earth but ultrasound is available on the ISS and the possibility of ultrasonographic metrics (e.g., optic nerve sheath diameter, CSF in the sheath) remain an area of continued research.…”
Section: Oct and Sansmentioning
confidence: 99%
“…Although several studies have been conducted on the effects of spaceflight on the soft tissue present in the skull, including reports of spaceflight-associated decreases in frontal and temporal gray matter volumes, increased somatosensory cortex, brain displacement within the skull, and ventricular volume expansion [32][33][34][35] , little is known on the effects of bone growth and remodeling. Previously, murine calvaria volume and thickness were reported to increase during the 15-day NASA Shuttle mission STS-131 36 ; however, when the same group repeated the spaceflight study with a longer mission duration (30 days), they observed no significant changes in murine calvaria bone thickness and volume when compared to ground controls 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors proposed that redistribution of CSF volume from the spinal canal to the cranium, in the absence of gravity, is the primary contribution to the increase in intracranial and orbital CSF volumes. As further proposed by the authors [13], unlike on Earth, where changing from supine to an upright posture reduces intracranial CSF volume due to a shift of CSF from the cranium to the spinal canal, in space, there is no force that intermittently reduces the cranial CSF volume and, thereby, allows reversed movement of CSF from the orbit back into the cranium. Therefore, during LDSF, it is highly unlikely that the CSF, once in the orbital CSF space, can change its direction of flow from the SAS of the ON toward the intracranial SAS [1].…”
Section: Discussionmentioning
confidence: 93%
“…In space, in the absence of gravity, bodily fluids shift in the cranial direction [12]. In a recent study using magnetic resonance (MR) imaging, Alperin and Bagci [13] found that the magnitude of SANS-associated ocular changes, namely globe flattening and ON protrusion, correlated significantly with increases in the orbital and ventricular CSF volumes. The authors proposed that redistribution of CSF volume from the spinal canal to the cranium, in the absence of gravity, is the primary contribution to the increase in intracranial and orbital CSF volumes.…”
Section: Discussionmentioning
confidence: 99%